2007
DOI: 10.1175/2007jas2239.1
|View full text |Cite
|
Sign up to set email alerts
|

The IMPROVE-1 Storm of 1–2 February 2001. Part III: Sensitivity of a Mesoscale Model Simulation to the Representation of Snow Particle Types and Testing of a Bulk Microphysical Scheme with Snow Habit Prediction

Abstract: A mesoscale model simulation of a wide cold-frontal rainband observed in the Pacific Northwest during the Improvement of Microphysical Parameterization through Observational Verification Experiment (IMPROVE-1) field study was used to test the sensitivity of the model-produced precipitation to varied representations of snow particles in a bulk microphysical scheme. Tests of sensitivity to snow habit type, by using empirical relationships for mass and velocity versus diameter, demonstrated the defectiveness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 52 publications
3
76
2
Order By: Relevance
“…This supports that similar findings for single case-studies of stratiform precipitation (e.g. Thompson et al, 2004;Colle et al, 2005;Woods et al, 2007) can be generalized to a broad range of synoptic conditions and can cautiously be interpreted as model improvements. Table 5 and Figure 8(a) and (b) provide an overview of the domain average and maximum 24-hour (0000-2400 UTC) accumulated surface precipitation for all experiments, and as derived from combined radar and rain-gauge information for the stratiform composite (blue symbols).…”
Section: Convective Compositesupporting
confidence: 85%
See 4 more Smart Citations
“…This supports that similar findings for single case-studies of stratiform precipitation (e.g. Thompson et al, 2004;Colle et al, 2005;Woods et al, 2007) can be generalized to a broad range of synoptic conditions and can cautiously be interpreted as model improvements. Table 5 and Figure 8(a) and (b) provide an overview of the domain average and maximum 24-hour (0000-2400 UTC) accumulated surface precipitation for all experiments, and as derived from combined radar and rain-gauge information for the stratiform composite (blue symbols).…”
Section: Convective Compositesupporting
confidence: 85%
“…From the higher precipitation rates in Figure 12, the more efficient removal of excess water vapour in ExpGS also likely enhances precipitation efficiency and hence surface precipitation. Woods et al (2007) found a similar impact of lower relative humidity with respect to ice and enhanced surface precipitation in a cold front simulation, when using non-spherical instead of spherical snowflakes. Similar to our findings for a broad range of stratiform cases, Colle et al (2005) also found a 10 to 15% increase in surface precipitation for frontal stratiform simulations when a temperature-dependent N 0S was applied as compared to using a fixed N 0S .…”
Section: Stratiform Case: 5 October 2008mentioning
confidence: 60%
See 3 more Smart Citations